Considerations in the Management Procedures of Malignant Large Bowel Obstruction; Surgical versus Conservative Management: Outcome and Prognostic Factors - Taha A. Baiomy; Mohamed Mahmoud Almeniawy; Mohamed Adel Sakr; Alaa Haggag; Shady E. Shaker; Mahmoud Sharafeddein; Mohamed Elbaz; Mahmod Ghoname; Mahmoud Sherbeiny; Ahmed Lotfy Sharaf; Amany M. Abdallah; Sherif Yehia Mohamed; et al. (Journal of Coloproctology)
Introduction Malignant obstruction of the large bowel is a common clinical presentation, particularly in terminal cancer patients. Urgent resection and surgical diversion were the treatments of choice.